Identification of Substance Abuse Among Children in a Pediatric Emergency Department - Nükhet Aladağ Çiftdemir; Tuba Eren; Yasemin Karal (Journal of Pediatric Research, 2020)

(untitled)
Aim:Illicit substance use is a worldwide important public health problem with increasing substance abuse rates and decreasing starting age. In this study, our aim was to determine the complaints of the patients in pediatric emergency department (PED) admission in order to increase awareness about substance abuse.Materials and Methods:The data of this cross-sectional study was gathered from those patients admitted to a PED with complaints of substance abuse and patients without a history of substance abuse, but with a positive urine drug test. A screening urine test was used for the qualitative determination of drug substances. If positive, a quantitative liquid chromatography integrated mass/mass spectrometry test was ordered for confirmation.Results:A total of 17 patients presented to the emergency department. The most frequent symptoms were unstable cognitive conditions and tachycardia. Laboratory analyses showed high creatine kinase-MB. Synthetic cannabinoids were the most frequently detected substance in urine screening and confirmation tests. Twenty-nine percent of patients were hospitalized and no mortality was observed.Conclusion:The use of illegal substances has increased in teenagers. Emergency department doctors must be informed and trained regarding substance abuse since patients frequently presented to the emergency department with cognitive malfunctions. Also, it should be remembered that patients may present with symptoms concerning various organ systems.